Risk Analysis of the Packing Process at the Logistics Department of PT. XYZ used REBA method - Lutfan Nabil; Said Salim Dahda (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2022)
PT. XYZ is a company that produces automotives and is one of the largest in Asia. PT. XYZ produces various types of springs, both leaf springs and conch springs which have been licensed from Mitsubishi Steel Manufacturing, Japan. Products from PT. XYZ will be exported to several countries such as the United States, Japan and India. In shipping can not be separated from the packaging process. In the packing process, it is found that the work posture is not good so that it can trigger complaints of Musculoskeletal Disorders. This study aims to determine the level of risk and work posture of workers. The method used is the REBA method, the results obtained in this study are with a grand score of 10 which indicates that work posture must be improved as soon as possible.